Karakteristik fisiko kimia sabun lembaran berbasis minyak sawit dengan penambahan gel dan ekstrak kulit lidah buaya - Narsih Narsih; Desdy Hendra Gunawan (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
The use of aloe vera to make soap enriches existing soap product variants. This research makes soap from aloe vera by utilizing gel and peel extract, which are processed separately and characterized by each soap produced. This research aimed to determine the physical and chemical characteristics of sheet soap produced from palm oil added with gel and palm oil added with aloe vera peel extract. The research results obtained from the chemical side of the soap water content parameters contained 1 sample that did not meet the SNI 3532:2016 standard, i.e., in the treatment of adding 25% aloe vera gel to 15.29%. In contrast, the other samples met the standard with a 9.24 – 13.33% water content range. In the test, the free alkali content did not meet SNI standards because the data obtained from all treatments was above 0.1%, while the pH was in the range of 8.5-9.8, and foam stability was 74-86%. Organoleptic testing of soap from both ingredients did not cause reddish and itchy reactions, meaning it did not irritate the skin, while testing for color, texture, and aroma gave no significantly different effects for all samples